Pengaruh Alat Ukur Efisiensi Penggunaan Modal Kerja terhadap Rentabilitas Ekonomis - R. Hery koeshardjono (Ecobuss, 2015)
The aim of study is to analyse the measuring instrument of efficiency use of working capital to economic rentability at Koperasi Karyawan Keluarga Besar Kertas Leces (K4L). The method is used the ratio analysis and statistical analysis with the source of Responsibility reporting of year 2000 up to year 2011 (12 year). The finding of this study is to show that the measuring instrument of efficiency use of working capital with Return on Working Capital (X1), Sales on Net Working Capital (X2) with the examination of significant variable (Uji-t) shows the measuring instrument of efficiency use of working capital with Return on Working Capital (X1) have an effect on by significant to economic rentability (Y) at Koperasi Karyawan Keluarga Besar Kertas Leces (K4L). While the examination of accuracy model (Uji-F) for the measuring instrument of efficiency use of working capital have an effect on the significant to economic rentability Koperasi Karyawan Keluarga Besar Kertas Leces (K4L) . The confencientcy’s determination is more high influence to variable measuring instrument use of working capital economic rentability, and other s variable out off. Keywords: efficiency, working capital, economic rentability